Réalisation d'un Système de contrôle et commande de remplissage des Réservoirs - BOUHOREIRA Abdelmalek; ZAID Messaoud; KHEDIR Nourredine (Université Echahid Hama Lakhdar- Eloued, 2025)
Our work is focused on automation. We released a project for an automated tank filling monitoring and control system using Arduino. We began an exploratory study on the causes of disasters and accidents resulting from the failure of liquid tank filling and monitoring systems worldwide, as well as the economic, human, and environmental consequences of these accidents. After analyzing these reasons, we chose the idea of implementing this system based on monitoring the liquid level inside the tank using an ultrasonic sensor. We took into consideration the low cost of implementing the project, as well as the accuracy and reliability of the system's performance, while also considering that the system can be used in industrial and domestic applications and for various types of liquids. يندرج عملنا هدا ضمن مجال الاتمتة فقد قمنا بإنجاز مشروع نظام آلي لمراقبة وتحكم في ملء الخزانات باستخدام الأردوينو. بدانا العمل بدراسة استكشافية حول أسباب الكوارث والحوادث الناجمة عن فشل أنظمة مراقبة وتحكم في ملء خزانات السوائل في العالم وكدلك دراسة أسباب ونتائج هده الحوادث اقتصاديا وبشريا وبيئيا. من خلال تحليل هده الأسباب اخترنا فكرة انجاز هدا النظام القائم على مراقبة مستوى السائل داخل الخزان عن طريق مستشعر الأمواج فوق صوتية. بحيث نأخذ بعين الاعتبار التكلفة المنخفضة لإنجاز المشروع وكدلك الدقة والموثوقية في أداء النظام مع الأخذ بعين الاعتبار ايضا ان النظام يمكن استخدامه في المجالين الصناعي والمنزلي ولمختلف أنواع السوائل.
Master's thesis in electromechanics.2025
Keywords: Arduino; tank; control system; control; filling; أردوينو، خزان، نظام تحكم، تحكم، تعبئة